Unmasking Disaster Accountability: Corruption Networks and The Psychology of Social Capital Fraud in Indonesia - Prasetyo, Whedy; Sulistiyo, Agung Budi (Jurnal Kajian Akuntansi, 2024)
This study explores the ethical and psychological dimensions of fraud within disaster social capital, with a particular focus on corruption networks during environmental crises in Indonesia. It investigates how the manipulation of aid distribution—originally intended to support collective welfare—erodes accountability and transforms moral norms. Drawing on in-depth qualitative insights from a senior academic in disaster governance and a high-ranking official at the National Disaster Management Agency, this research uncovers how the mismanagement of disaster relief funds not only facilitates corruption but also blurs the ethical boundary between public duty and private gain. Two prominent patterns emerge: first, aid allocators engage in corrupt practices that weaken communal trust networks; second, the misappropriation of funds becomes normalized as personal entitlement, institutionalizing unethical behavior. This case highlights how the distortion of social customs and consensus can be used to rationalize unethical conduct, ultimately weakening legal structures and ethical integrity. The findings offer critical implications for ethics education in public administration and business, emphasizing the urgent need to embed moral reasoning and accountability frameworks in disaster response systems.